Renal and Vascular Functional Decline in Aged Low Birth Weight Murine Adults - May M. Rabadi; Marella R. Verde; Mia Camilliere; Nicholas Vecchio; Sharath Kandhi; Miroslav Sekulic; Michael S. Wolin; Brian B. Ratliff (Kidney & Blood Pressure Research)
Introduction: Maternal undernutrition (MUN)-induced low birth weight (LBW) neonates are susceptible to the development of high blood pressure and kidney disease later in life, although the underlying pathological causes remain unclear. The study here investigated the role of renal oxidative stress, impairment of vascular function, and altered sensitivity to angiotensin II (Ang II) as factors that contribute to these pathologies in aged LBW mice. Methods: LBW offspring were generated using a combined protein and caloric restricted MUN mouse model. The resulting LBW offspring were examined 1 year after birth for mean arterial blood pressure (MABP) (carotid artery catheterization), renal blood flow (RBF) (laser Doppler flowmetry), glomerular filtration rate (GFR) (sinistrin clearance), vasoreactivity (myograph), renal vascular density (CD31 staining), and reactive oxygen species (ROS) (ROS probes). Immunoblotting examined Ang II type 1 receptor (AT1R), soluble guanylate cyclase (sGC), and antioxidant systems. Pharmacological agents delivered to animals included the sGC stimulator δ-aminolevulinic acid (ALA), the AT1R inhibitor losartan, the antioxidant ethyl pyruvate (EP), and the toll-like receptor 4 inhibitor TAK242. Results: After 1 year, MABP was increased, while RBF, GFR, vascular reactivity, renal vascular density, and sGC were all reduced in the LBW aged adult. All four pharmacological agents improved MABP, RBF, GFR, vascular density, and vascular reactivity. Renal ROS was increased in the LBW adult but was reduced by ALA, EP, and TAK242 treatment. AT1R was upregulated in the LBW adult, while sGC was decreased, an effect reversed by ALA treatment. Endogenous antioxidant systems, including SOD1, catalase, and glutathione were downregulated in the LBW adult. Conclusion: MUN-induced LBW mice experience increased Ang II sensitivity and oxidative stress. The increased Ang II sensitivity and ROS generation influences vascular density and reactivity, which drive an increase in MABP, and a concomitantly decrease in RBF and glomerular filtration. Pharmacological intervention that inhibits AT1R, enhances levels of sGC, reduces ROS, or inhibits toll-like receptor 4 improves vascular and renal function in the LBW adult.